86.7k views
1 vote
Explain how you would solve the equation 3x + 4 - 2x = 6x + 2 - 5x + 2

Explain how you would solve the equation 3x + 4 - 2x = 6x + 2 - 5x + 2-example-1
User Andurit
by
6.2k points

1 Answer

7 votes

Answer:

Both sides are true.


\mathrm{Group\:like\:terms}\\3x-2x+4=6x+2-5x+2\\\mathrm{Add\:similar\:elements:}\:3x-2x=x\\x+4=6x+2-5x+2\\\mathrm{Group\:like\:terms\:again}\\x+4=6x-5x+2+2\\\mathrm{Add\:similar\:elements:}\:6x-5x=x\\x+4=x+2+2\\\mathrm{Add\:the\:numbers:}\:2+2=4\\x+4=x+4

Hope this helps and have a great day!!!


Sofia

User Kisha
by
5.6k points